Multi-stakeholder perception analysis of the status, characteristics, and factors affecting small-scale carp aquaculture systems in Bangladesh - Rossignoli, Cristiano M.; Lozano Lazo, Denise P.; Barman, Benoy Kumar; Dompreh, Eric Brako; Manyise, Timothy; Wang, Quanli; Dam Lam, Rodolfo; Moruzzo, Roberta; Paz Mendez, Alvaro; Gasparatos, Alexandros (Frontiers in Sustainable Food Systems, 2023)
Inland aquaculture caters for the food and livelihoods of millions of small-scale producers across the global South. Very diverse interventions from national governments, civil sector and international organizations have been seeking to enhance the performance of small-scale aquaculture systems. However, many of these efforts are constrained by the general lack of information regarding the status and characteristics of the sector. In many cases, data are unavailable, highly aggregated or outdated, failing to provide a clear picture of the situation on the ground to inform relevant efforts. Bangladesh is one such country, where, on the one hand, aquaculture is extremely important for national economic growth, rural development and food and nutrition security, but on the other hand suffers from a general lack of quality data to inform relevant actions. In this study, we report the findings from eight workshops with 215 stakeholders in the Bangladesh small-scale carp aquaculture sector. By leveraging the expertise of the participants, we obtain an overarching picture of the characteristics of small-scale carp production models around the country. The findings suggest a large variability of production models and intensification, mainly based on polyculture with main species being rohu, catla and mrigal. These systems have been roughly categorized in four types characterised by different levels of intensification and dominant species, which are present across the country with varied socio-economic, infrastructure and environmental conditions. The study also identified an unfolding shift from subsistence-based to commercially oriented production in the last years. In terms of market preference, quite different carp attributes are valued among small-scale producers across the country, with large size of carp, rapid growth and availability of improved strains being the most valued. Since aquaculture, and particularly carp aquaculture, is important for rural development by sustaining households’ income and livelihoods in different ways, we argue for the need to undertake more detailed studies to understand the characteristics and performance of these types of small-scale aquaculture systems. This will be indispensable for informing policies and actions that aim to target more effectively the different types of producers, and to improve the overall performance and sustainability of the sector.